Mengatasi Kesulitan Motorik Dan Daya Ingat Terhadap Lansia Di Rumah Bahagia Bintan - Dea Lestari; Aidiliza Safitri; Suryaningsih . (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
The Rumah Bahagia Bintan nursing home, established in 2007 in Bintan Regency, is experiencing motor and memory problems. This study investigates methods to address these issues in the elderly. To understand the elderly's problems, such as difficulty walking, balance, and memory loss due to aging, the researchers used a qualitative descriptive approach through documentation, interviews, and observation. The purpose of this study was to identify the types of motor and memory difficulties in the elderly, and to develop and evaluate interventions that could improve motor and cognitive abilities at Rumah Bahagia Bintan. This study used a qualitative approach with a case study design. Data were collected through direct observation, comprehensive interviews with the caretaker and elderly at the home, and documentation of daily activities. Furthermore, this study examined the use of simple exercise programs as interventions, such as elderly gymnastics, group activity therapy, and memory-enhancing games. To gain a better understanding of the changes occurring in the elderly, the data analysis technique used was thematic analysis. The results showed that routine interventions can improve the elderly's motor skills, such as balance and coordination, and also improve their short-term memory. Elderly individuals who consistently participated in the program demonstrated the ability to perform daily activities independently. In addition, being involved in group activities that involve social interaction also helps the psychological condition of the elderly, helping them to become more active, more confident, and have a better quality of life.